Investigating Research Streams of Conjoint Analysis: A Bibliometric Study - Thorsten Teichert; Edlira Shehu (BuR - Business Research, 2010)
Conjoint analysis (CA) is one of the most important methods for preference elicitation. In this paper we investigate the intellectual structure within the conjoint analytical research community. Analyses based on single papers provide a method-based overview of streams of conjoint research. By using novel bibliometric techniques in this field we complement findings of existing reviews. We use co-citation and factor analysis of the most cited articles in SSCI to identify the most important articles and research streams. Seven research streams are revealed which are visualized by means of multidimensional scaling. Tables and graphics reveal the disciplinary affiliations of contributors to CA, the special structure within the classes as well as links between them.
urn:nbn:de:0009-20-25062
Keywords: 650; conjoint analysis; bibliometric analysis; Conjoint-Analyse; Bibliometrie